Relationships between cystatin C and creatinine‐based eGFR with low tongue pressure in Japanese rural community‐dwelling older adults. Issue 5 (24th June 2022) - Kusunoki, Hiroshi; Hasegawa, Yoko; Tsuji, Shotaro; Wada, Yosuke; Tamaki, Kayoko; Nagai, Koutatsu; Mori, Takara; Matsuzawa, Ryota; Kishimoto, Hiromitsu; Shimizu, Hideo; Shinmura, Ken
Abstract: Background: Sarcopenia is prevalent in patients with chronic kidney disease (CKD), which is defined as a low estimated glomerular filtration rate (eGFR). It has been reported that oral hypofunction characterized by decreased tongue pressure is related to sarcopenia. Although there are several previous reports regarding the association of renal dysfunction with oral hypofunction characterized by low tongue pressure, the association between tongue pressure and renal function is not fully understood. Methods: This cross‐sectional study included 68 men aged 79.0 ± 4.8 years and 145 women aged 77.3 ± 5.4 years from a rural area in Hyogo Prefecture, Japan. We examined the relationships between cystatin C‐based CKD (CKDcys), creatinine‐based CKD (CKDcre), ratio of cystatin C‐based GFR (eGFRcys) divided by creatinine‐based GFR (eGFRcre): eGFRcys/eGFRcre, and tongue pressure in community‐dwelling older adults. Results: Tongue pressure was significantly lower in participants with CKDcys than in those without CKDcys in men and women. However, there were no significant differences in tongue pressure with or without CKDcre. Tongue pressure was significantly lower in participants with eGFRcys/eGFRcre <1.0, than in those with eGFRcys/eGFRcre ≧ 1.0 in men. According to the receiver operating characteristic analysis, the optimal cut‐off value of tongue pressure for the presence of CKDcys was 36.6kPa, area under the curve (AUC) 0.74 (specificity 54.8%, sensitivity 84.6%) in men and 31.8kPa, AUC 0.65 (specificity 67.3%, sensitivity 60.5%) in women. Conclusions: CKDcys but not CKDcre is associated with low tongue pressure. In addition, a lower eGFRcys/eGFRcre ratio is a useful screening marker of low tongue pressure in community‐dwelling older adults.